1989
DOI: 10.1093/treephys/5.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Branch breakage under snow and ice loads

Abstract: Measurements were made on branches and trunks of Picea sitchensis (Bong.) Carr. to determine the relationship between (i) the bending moment at the bases of branches that cause breakage, and (ii) midpoint diameter cubed. The theory for cantilever beams was then used to calculate the basal bending moments and midpoint diameters of branches with different numbers of laterals and endpoint deflections, given previously measured values of Young's modulus, taper and weights of foliage and wood. Snow and ice loads (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…Less transient bending may also occur when loads such as rainwater, snow, fruit, and sometimes the shoot itself weigh branches down (Cannell and Morgan, 1989; Alméras et al , 2004). The common horticultural practice of artificially bending shoots of some species may have a positive qualitative and quantitative impact on flowering, fruit production, and maturation (Valinger, 1992; Kim et al , 2004; Han et al , 2007; Liu and Chang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Less transient bending may also occur when loads such as rainwater, snow, fruit, and sometimes the shoot itself weigh branches down (Cannell and Morgan, 1989; Alméras et al , 2004). The common horticultural practice of artificially bending shoots of some species may have a positive qualitative and quantitative impact on flowering, fruit production, and maturation (Valinger, 1992; Kim et al , 2004; Han et al , 2007; Liu and Chang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Under suitable meteorological and topographic conditions, tree stems and branches become coated with ice. Tree crowns are injured when the added weight of ice exceeds the threshold for breaking stress of stems and branches (Cannell and Morgan 1989). Ice storms geographic extent and strongly localized with respect to elevation and directional exposure.…”
Section: Introductionmentioning
confidence: 99%
“…More woody material is then allocated to these areas of higher strain through greater cell division of the vascular cambium, which results in increased numbers of tracheids (Telewski and Jaffe 1986a) and a reduction in longitudinal bending strains. These increases in branch diameter offer significant benefits in terms of reducing the risk of mechanical failure as Cannell and Morgan (1989) have shown that simple beam theory does hold for branches, and that the bending moment at failure is linearly proportional to the cube of diameter.…”
Section: Discussionmentioning
confidence: 99%